Barriers to implementation of project monitoring and evaluation: a study of corporate social responsibility projects of large organisations in the Western Region - Mensah, Abraham (KNUST, 2025)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of requirements for the award degree of Master of Science in Project Management